Porous composite material based on liquid glass - Miryuk, О.А. (Kompleksnoe Ispolzovanie Mineralnogo Syra = Complex use of mineral resources, 2022)
The article presents the results of experimental studies of a composite material obtained on the basis of liquid glass and mineral fillers of technogenic origin. The structure of the composite material is formed by porous granules bonded with a liquid-glass matrix. The porous filler is synthesized from a mixture of liquid glass and combined filler (cullet, flake overburden, coal mining waste, and ash microsphere). Regulation of composition and content of the filler in the raw mixture ensures porous granules production with a bulk density of 270 – 330 kg/m3. Analysis of mathematical models reflecting the dependence of the density and strength of the composite material on the composition of the moulding mixture allowed us to establish a reasonable ratio between the liquid glass and the filler, the matrix, and the porous filler. Optimal proportions of the composite material are characterized by a density of 450 – 600 kg/m3and compressive strength of at least 5.5 MPa. Strong adhesion of the liquid-glass matrix to the surface of the porous filler ensures the resistance of the composite material to diverse effects. The structure of the materials was studied by electron microscopy. The development of composite material is aimed at improving the energy efficiency of construction.